Assoc. Prof. Dr. Mohamad Nizam Jaafar represents AAGBS in international academic programme - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
Arshad Ayub Graduate Business School (AAGBS), Universiti Teknologi MARA (UiTM) proudly records the international academic engagement of Assoc. Prof. Dr. Mohamad Nizam Jaafar, who was invited to serve as a visiting lecturer at Walailak University International College (WUIC), Thailand, from 22 July to 2 August 2024. During this period, Assoc. Prof. Dr. Mohamad Nizam Jaafar delivered the course Digital Currency and Blockchain Technology, providing students with in-depth exposure to emerging financial technologies, blockchain systems, and digital currency applications. His involvement contributed significantly to enriching the academic experience of students through the sharing of expertise, practical knowledge, and global perspectives in this rapidly evolving field. This international teaching engagement reflects AAGBS's continued commitment to academic excellence, global collaboration, and knowledge exchange, while further strengthening the strategic partnership between AAGBS, UiTM Shah Alam and Walailak University International College.